Nutritional status and functional capacity of hospitalized elderly - Oliveira, Maria R. M. [UNESP]; Fogaca, Kelly C. P.; Leandro-Merhi, Vania A. (Biomed Central Ltd., 2009)
Background: The nutritional status of the aging individual results from a complex interaction between personal and environmental factors. A disease influences and is influenced by the nutritional status and the functional capacity of the individual. We asses the relationship between nutritional status and indicators of functional capacity among recently hospitalized elderly in a general hospital.Methods: A cross-sectional study was done with 240 elderly (women, n = 127 and men, n = 113) hospitalized in a hospital that provides care for the public and private healthcare systems. The nutritional status was classified by the MNA (Mini Nutritional Assessment) into: malnourished, risk of malnutrition and without malnutrition (adequate). The functional autonomy indicators were obtained by the self-reported Instrumental Activity of Daily Living (IADL) and Activity of Daily Living (ADL) questionnaire. The chi-square test was used to compare the proportions and the level of significance was 5%.Results: Among the assessed elderly, 33.8% were classified as adequate regarding nutritional status; 37.1% were classified as being at risk of malnutrition and 29.1% were classified as malnourished. All the IADL and ADL variables assessed were significantly more deteriorated among the malnourished individuals. Among the ADL variables, eating partial (42.9%) or complete (12.9%) dependence was found in more than half of the malnourished elderly, in 13.4% of those at risk of malnutrition and in 2.5% of those without malnutrition.Conclusion: There is an interrelationship between the nutritional status of the elderly and reduced functional capacity.